2017
DOI: 10.1186/s12917-017-1031-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of Polybrominated Diphenyl Ethers (PBDEs) and Polychlorinated Biphenyls (PCBs) with Hyperthyroidism in Domestic Felines, Sentinels for Thyroid Hormone Disruption

Abstract: BackgroundHyperthyroidism is the most common endocrine disorder observed in domestic felines; however, its etiology is largely unknown. Two classes of persistent organic pollutants, polybrominated diphenyl ethers (PBDEs) and polychlorinated biphenyls (PCBs) are known to interfere with thyroid hormone (TH) signaling and regulation; thus, it is postulated that they contribute to the etiopathogenesis of feline hyperthyroidism and pose a risk to humans and other species. In this case-control study, the concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
17
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
1
17
1
Order By: Relevance
“…Our data agrees with these trends with the Bay Area having the highest concentrations of BDE-47, -99, and -100. Our results also agree with a recent study investigating PBDE congener profiles in felines from California ( Walter et al, 2017 ). In contrast, a feline study conducted in Sweden identified BDE209 and BDE207 as the most prevalent BDE congeners with BDE99 accounting for only 13% total body burden, compared to 44% in a US population ( Kupryianchyk et al, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our data agrees with these trends with the Bay Area having the highest concentrations of BDE-47, -99, and -100. Our results also agree with a recent study investigating PBDE congener profiles in felines from California ( Walter et al, 2017 ). In contrast, a feline study conducted in Sweden identified BDE209 and BDE207 as the most prevalent BDE congeners with BDE99 accounting for only 13% total body burden, compared to 44% in a US population ( Kupryianchyk et al, 2009 ).…”
Section: Discussionsupporting
confidence: 93%
“…Domestic pets, such as cats and dogs, share much of their environment with humans, thus they may serve as biosentinels of potential human health hazards by providing data on the contaminants within a defined area and serving as a proxy of human exposure to these environmental contaminants ( Venier & Hites, 2011 ; Walter et al, 2017 ). Even though pets and their owners share the same air, water, and housing, pets are usually free of lifestyle factors that may confound associations with true risk factors in humans, such as tobacco use, alcohol and caffeine consumption, poor diet, insufficient physical activity, and low social class ( Schmidt, 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Their involvement in the aetiology of hyperthyroidism has recently been disputed, at least in Australian cats [ 46 ]. However, several other studies have suggested that PBDEs may be involved in the aetiopathogenesis of the disease, at least in Europe and California [ 31 33 ]. Alternatively, clients owning cats that are kept predominantly indoors may be more observant of clinical signs associated with hyperthyroidism and thus more likely to present for veterinary attention.…”
Section: Discussionmentioning
confidence: 99%
“…Undoubtedly, there are many potential thyroid disruptors that cats may be exposed to, either through their diet or from the environment. Several factors have since been implicated in the development of hyperthyroidism including dietary iodine intake [ 27 ], soy isoflavone excess [ 28 , 29 ], exposure to bisphenol A from pop top or ring pull cans [ 8 , 30 ] and polybrominated diphenyl ethers (PBDEs) from the environment [ 31 33 ]. Overall the association between diet and development of hyperthyroidism is controversial and exemplified by the presence of the same potential dietary risk factors in areas of low prevalence of the disease [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies have suggested that pet cats are suitable bio-sentinel for human exposure to household chemicals including PBDEs [ 7 , 8 , 19 , 26 ]. Feline hyperthyroidism associated with increased PBDE levels in cat serum have been reported worldwide [ 26 , 30 , 40 ], but the information on CYP expression in cat exposed to PBDE has not been provided. The objective of this study was therefore to investigate the CYP mRNA expression in cats treated BDE-209 for long-term exposure.…”
mentioning
confidence: 99%